Carbon dioxide and oxidative techniques to improve growth and yield of beetroot, Swiss chard and green beans - Marais, D. (Diana) (University of Pretoria, 2023)
Dissertation (MSc Agric (Horticultural Science)) --University of Pretoria, 2023.